INFORMATIKA SABAQLARÍ SÍPAT NÁTIYJELIGIN ASÍRÍWDA MASHQALALÍ TÁLIM TEXNOLOGIYALARÍNAN PAYDALANÍW - Turmanov, Q.A. (SCIENCE and SOCIETY, 2024)
This article examines the use of group learning in computer science and information technology classes. It also provides suggestions and recommendations for the effective use of problem-based educational technologies in computer science and information technology classes.